Considerations in the development of generic disease therapies for multiple sclerosis. Issue 4 (August 2016) - Hua, Le H.; Cohen, Jeffrey A.
Abstract: Purpose of review: Medication prices are a major contributor to the high cost of care for multiple sclerosis (MS). The patents for some of the initial injectable therapies for relapsing MS recently expired, permitting development, regulatory approval, and marketing of generic alternatives with the potential for lower prices and cost savings to payers and patients. Recent findings: A generic version of glatiramer acetate 20 mg administered by daily subcutaneous injection recently received regulatory approval in the United States. Two additional generic versions of glatiramer acetate have been submitted for regulatory review. The development and testing of generic disease-modifying therapies for MS such as glatiramer acetate, which are complex molecules, present several complicating factors. Summary: This article provides background on the development of generics and reviews the status of generic glatiramer acetate.